The agreement between self-reported cervical smear abnormalities and screening programme records. - Canfell, K; Beral, V; Green, J; Cameron, R; Baker, K; Brown, A (2006)
SETTING: The Million Women Study is a cohort study of women aged 50-64 years in England and Scotland. As a component of the follow-up questionnaire, participants were asked to indicate if they had an abnormal cervical smear in the previous five years. This study compared self-reported cervical abnormalities with screening records obtained from the National Health Service Cervical Screening Programme. METHODS: For 1944 randomly selected Million Women Study participants in Oxfordshire, screening records were assessed over a six-year period prior to the date of self-reporting. The six-year period was chosen to allow for errors in the recall of timing of abnormal smears. RESULTS: A total of 68 women (3.5%) had a record of at least one equivocal or abnormal smear within the last six years, whereas 49 women (2.5%) self-reported an abnormality. There was a strong trend for an increased probability of self-reporting a history of an abnormal smear as the severity of the recorded abnormality increased (P <0.001). For women with an NHS record of borderline dyskaryosis, mild dyskaryosis, or moderate dyskaryosis/severe dyskaryosis/invasive cancer, the proportions reporting an abnormality were 40%, 58% and 77%, respectively. For women with negative and inadequate smears, the proportion self-reporting an abnormality were 0.6% and 0.7%, respectively. CONCLUSIONS: These results indicate that among women whose screening programme records show an abnormal smear, the proportion self-reporting an abnormality increases with the severity of the recorded lesion. Almost all women with a record of negative or inadequate smear(s) correctly interpret the result and do not self-report an abnormality.